Stress Pattern and Deformation in Mid-palatal Suture and Posterior Dentoalveolar Area With Two Different Types of Rapid Maxillary Expansion Appliances: A Finite Element Method Study. Issue 3 (July 2021) - Shrivastava, Nitya; Thukral, Rakesh; Garg, Ashish; Tripathi, Amit; Marothiya, Sunita
Objective: The study was conducted to evaluate stress pattern and deformation in mid-palatal suture and posterior dentoalveolar area during maxillary expansion therapy with two different types of rapid maxillary expansion by finite element method study. Methods and Methodology: The finite element analysis was performed on a model of maxilla, with narrow maxillary base and teeth digitally reconstructed, based on CBCT images, acquired by child (age 12.5 years) but not in permanent dentition stage from available pool data. Result: More amount of stress was observed in mid-palatal suture and posterior dental alveolar area by using the Hyrax appliance as compared to the Haas appliance. Stress pattern evaluated in mid-palatal suture depicts maximum stress concentration on the anterior region of mid-palatal suture at the position of incisive papilla. Deformation in maximum quantity is observed in central incisors. Maximum stress generation and deformation are observed in lingual region of premolar and molar areas. Minimum stress generation and deformation are observed in the posterior part of last molars. Conclusion: Hyrax produces more stress and deformation in mid-palatal suture as well as in the posterior alveolar segment in comparison to Haas appliance. Better results in the immediate skeletal response were obtained by the Hyrax-type expander as compared to the Haas type.